2009
DOI: 10.1111/j.1741-6612.2008.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Mainstream versus ethno‐specific community aged care services: It's not an ‘either or’

Abstract: Approximately 16% of the Australian population speak a language other than English at home. Older people from culturally and linguistically diverse (CALD) backgrounds face many barriers to accessing services which may explain their under-utilisation of community aged care services. The aim of this review is to critique the literature related to the delivery of community aged care services to people from CALD backgrounds. The merits of a partnership model approach are highlighted, in addition to key points for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…Communication with the welfare system may be a barrier because of language difficulties (Egeblad 2005;Radermacher et al 2009;Denktas 2011;Hurley et al 2012). A qualitative interview study of 29 immigrants in Copenhagen and 3 of their relatives (Dupont and Fatum 2007) concluded that older immigrants and their relatives have limited knowledge of the availability of assistance from municipal elder care services.…”
Section: Discussionmentioning
confidence: 99%
“…Communication with the welfare system may be a barrier because of language difficulties (Egeblad 2005;Radermacher et al 2009;Denktas 2011;Hurley et al 2012). A qualitative interview study of 29 immigrants in Copenhagen and 3 of their relatives (Dupont and Fatum 2007) concluded that older immigrants and their relatives have limited knowledge of the availability of assistance from municipal elder care services.…”
Section: Discussionmentioning
confidence: 99%
“…We also anticipated that help-seeking pathways would depend on age, as barriers to accessing health services are greater for older than younger people (Radermacher et al, 2009). Although not evident within the West African sample, the older less-educated Australian women were more likely than other women to seek help from a general practitioner for stress.…”
Section: Downloaded By [Colorado College] At 15:17 14 October 2014mentioning
confidence: 98%
“…It was hypothesized that barriers to accessing health services would be greatest for women with few years of schooling and with only a short period of acculturation. As older people, particularly those from culturally and linguistically diverse backgrounds, face many barriers to accessing health services (Radermacher, Feldman, & Browning, 2009), it was anticipated that the older women would report more barriers than younger women to accessing these services.…”
mentioning
confidence: 99%
“…In New Zealand, studies focusing on South Korean, Chinese, South African, and Indian migrants have been undertaken (Alpass et al, 2007; DeSouza, 2006; Park & Kim, 2013), revealing migration issues and processes affecting migrants’ psychological well-being and their experiences of growing old in New Zealand. Furthermore, there has been an increase in empirical work documenting the complex health and well-being needs of older migrants, who are culturally and linguistically diverse (Al Abed, Davidson, & Hickman, 2014; Radermacher, Feldman, & Browning, 2009). Ageing in general is accompanied by inevitable and complex co-morbidities, including physiological and psychosocial health-related issues.…”
Section: Introductionmentioning
confidence: 99%